Simultaneous detection of CO2 and CO in engine exhaust using multi-mode absorption spectroscopy, MUMAS - Thompson, A; Northern, H; Williams, B; Hamilton, M; Ewart, P (Elsevier, 2014)
Multi-mode absorption spectroscopy, MUMAS has been employed for the simultaneous detection of CO2 and CO. MUMAS signatures were recorded using a diode-pumped Er:Yb:glass microlaser emitting a multi-mode spectrum in the region of 1.57 μm. The ratio of CO2:CO concentrations in a calibration gas was measured to within the manufacturers uncertainty of ±1.4%. Both gases were also detected and the ratio of their concentrations measured in the exhaust gas of a SI internal combustion engine under varying conditions of fuel/air ratio and compared with measurements using a commercial gas analyser. Standard errors on the mean for the measurements were in the range 0.4-0.8%. The detection limit for CO partial pressure was determined to be 0.15 mbar in 100 mbar total pressure. © 2014 Elsevier B.V.